Poroelastic effects on rupture propagation across fault stepovers - Huang, Luyuan (2025)
The role of poroelasticity in influencing the frequency of ruptures jumping through strike-slip stepovers remains unclear. To understand how poroelastic effects govern long-term rupture behavior in strike-slip fault systems with stepovers, we conduct earthquake sequence simulations incorporating undrained pore pressure responses across the full spectrum of Skempton's coefficient. Our findings reveal that Skempton's coefficient significantly affects the effective normal stress, which can either cause fault clamping or unclamping, and ultimately influences rupture propagation across fault stepovers. The likelihood of rupture jumping is predominantly determined by Skempton's coefficient and the width of the stepover, with Skempton's coefficient showing an approximately linear relationship to the critical jumpable step size. Specifically, a higher Skempton's coefficient facilitates rupture jumping across fault segments, even over larger stepover distances. Analytical solutions involving dislocation and Skempton's coefficient provide practical methods for evaluating pore pressure changes and associated seismic hazards near fault stepovers. Our statistical analysis identifies a critical jumpable width of 4.4–5.1 km due to static stress transfer, assuming a typical range of Skempton's coefficient for compressional stepovers, beyond which ruptures are unlikely to propagate. This study underscores the potential of using physics-based earthquake sequence models to reflect statistical fault rupture behaviors. Given that multi-segment earthquake ruptures present challenges in assessing maximum rupture lengths, our findings offer crucial insights into the role of poroelastic effects and the conditions that facilitate or limit rupture propagation across fault stepovers.